KEBIJAKAN PEMERINTAH DAERAH KABUPATEN SINTANG TERHADAP PEMBATASAN HAK PETANI LADANG TRADISIONAL DALAM PEMBUKAAN LAHAN DENGAN MEMBAKAR - Redin - (Universitas Kapuas Sintang, 2020)
Sintang district’s regional government has issued its decree no. 57 year 2018 about the proposed land opening ceremony for people in sintang district. Such policies restrict the rights of local people and their generation to burn-through what has always been done according to local policy values. The study used the normativejuridical approach method, conducted to identify and analyze in detail the restriction of traditional field farmers’ rights in land opening by burning that had been set in the 57th year 2018 regents’ rule and the local farmer’s traditional field wisdom in clearing by burning. Studies show that in article 6 of the 57th year 2018 regaining rule, regulatory the traditional farmers’ rights to perform land clearing by burning. The complex requirements of the conditional provisions made it difficult for traditional farmers to carry out the traditional traditions passed down in the indigenous dayak community in sintang district.